2020
DOI: 10.2478/ijame-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation and Eckert Number on MHD Flow with Heat Transfer Rate Near a Stagnation Point Over a Non-Linear Vertical Stretching Sheet

Abstract: This work investigates the effects of radiation and Eckert number on an MHD flow with heat transfer rate near a stagnation-point region over a nonlinear vertical stretching sheet. Using a similarity transformation, the governing equations are transformed into a system of ordinary differential equations which are solved numerically using the sixth order Runge-Kutta method with shooting technique. Tabular and graphical results are provided to examine the physical nature of the problem. Heat transfer rate at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With the help of the similarity technique, it is again transformed into an initial value problem described by Ali et al [ 46 , 47 ] and Uddin and Nasrin [ 48 ]. Using numerical methods, we successfully solve coupled non-linear ODEs [ [24] , [25] , [26] , [27] ] with boundary conditions [ 28 , 29 ] applying the shooting technique.…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of the similarity technique, it is again transformed into an initial value problem described by Ali et al [ 46 , 47 ] and Uddin and Nasrin [ 48 ]. Using numerical methods, we successfully solve coupled non-linear ODEs [ [24] , [25] , [26] , [27] ] with boundary conditions [ 28 , 29 ] applying the shooting technique.…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…They observed that microparticles in the fluid caused it to absorb more heat, increasing the fluid temperature through viscous dissipation and heat generation. Fenuga et al [ 28 ] considered the impact of the Eckert number and radiation parameter over an MHD flow with a heat transmission rate close to a stagnation point. Eckert number and radiation caused a lessening heat transmission rate at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Consider η = rπ(x, t) as in (58), i.e., where π(x, t) = (Bt + A) n for n = − 1 2 and Γ 1 = Γ 1 (x, t),Γ 2 = Γ 2 (x, t). In this case and by further assuming C 3 to be unity, (66) gives…”
Section: Case (C)mentioning
confidence: 99%
“…(i) The ferromagnetic interaction parameter β = 0 − 10 as in [12,13,39,40,49]; (ii) The magnetic field parameter Mn = 1 , 3 , 5 as in [13,40,49,57]; (iii) The Prandtl number Pr = 21 , 23 , 25 as in [13,40,49]; (iv) The radiation parameter Nr = 0.1 , 0.2 , 0.5 , 1, 1.5, 3 as in [57]; (v) The Eckert number Ec = 0.001 , 0.002, 0.003, 0.01 , 1 as in [58]; (vi) The volume fraction φ = 0 , 0.05 , 0.1 , 0.2 as in [49].…”
Section: Mnmentioning
confidence: 99%